IDENTIFIKASI FAKTOR PEMBENTUK PERILAKU PENCARI KERJA GENERASI Z DI INDONESIA: IDENTIFICATION OF BEHAVIOR FACTORS OF GENERATION Z JOB SEEKERS IN INDONESIA - Hanifah; Prabu Wardono (School of Business, Bogor Agricultural University (SB-IPB), 2020)
This study aims to identify the factors shaping the behavior of generation Z job seekers in Indonesia. This research was conducted in generation Z (birth year 1995- 2010) by involving 150 respondents divided into 50 student respondents each in the fields of technology, creative, and business, most of them lived in Jakarta and Bandung. The questionnaire was distributed online via google docs. This research uses quantitativemethods. The form of a questionnaire outlined in online form via google docs with a total of 33 Likert scale question items. Confirmatory factor analysis (CFA) is used to determine the factors shaping the behavior of generation Z job seekers in Indonesia. The results of this study indicate that the dimensions of intrinsic, extrinsic, altruistic, status, and social work values are able to measure the latent variables of generation Z work behavior. In this study, it was found that the three dimensions that had the greatest contribution were the altruistic, status, and social work values. The social dimension is the same as the research findings in Turkey, while the altruistic and social dimensions are the same as the research findings in India. This study recommends that the concept of workspace needs to pay attention to the distance between employees because generation Z wants a workplace where they want to have a good relationship with their colleagues and can help each other, when observed from the altruistic and social work value factors. There should also be a refuge room facility so that employees can focus more on completing their work which can increase their capacity, as indicated by to the status factor. Keywords: workspace, work behavior, work value, generation z, confirmatory factoranalysis